Edukasi Pengelolaan Obat Melalui DAGUSIBU untuk Mencapai Keluarga Sadar Obat - Wahida Hajrin; Candra Dwipayana Hamdin; Dyke Gita Wirasisya; Gusti Ayu Putu Sri Erwinayanti; Raisya Hasina (Universitas Mataram, 2020)
Abstract: The high ratio of population in Pamenang, Tanjung, and Gangga sub-districts compared to existing facilities and health workers is a very principle problem related to health education for the community, including information about medicine. One of whichis about the correct methods of how to get, use, save, and dispose medicines which is abbreviated with the DAGUSIBU program, including how to use special medicines. The aim of this socialization was to educate the patients in the public health center in Pemenang, Tanjung, and Gangga sub-districts about DAGUSIBU. The DAGUSIBU socialization program was carried out through the delivery of material, discussions, questions and answers, and demonstration by the audience and Pharmacists. Participants that incidentally were patients in public health centrewere very enthusiastic about this program as evidenced by the activeness of the participants in asking questions and answering questions about DAGUSIBU. Keywords: DAGUSIBU, socialization, Pemenang, Tanjung, Gangga, medicine